Character compass : how powerful school culture can point students towards success - Seider, Scott (Cambridge, Mass. : Harvard Education Press, 2012)
The author "offers portraits of three high-performing urban schools that have made character development central to their mission. [The book] highlights each school's unique approach to character development and shows how qualities like empathy, integrity, perseverance, and daring can nurture student success"--P. 4 of cover
"In Character Compass, Scott Seider offers portraits of three high-performing urban schools in Boston, Massachusetts that have made character development central to their mission of supporting student success, yet define character in three very different ways. One school focuses on students' moral character development, another emphasizes civic character development, and the third prioritizes performance character development. Drawing on surveys, interviews, field notes, and student achievement data, Character Compass highlights the unique effects of these distinct approaches to character development as well as the implications for parents, educators, and policymakers committed to fostering powerful school culture in their own school communities." -- Publisher's website.
Introduction -- Dimensions of character. Character and community meeting -- Moral character at Boston prep. Do the right thing -- Walk in another's shoes -- Performance character at Roxbury prep. Prepare to perform -- Effort determines success -- Civic character at Pacific Rim. Make a contribution -- Be the change -- Conclusion. Building powerful school culture through character development.
Includes bibliographical references (p. 255-271) and index.
Keywords: Moral education -- Massachusetts -- Boston; Academic achievement; Character